2016
DOI: 10.1002/lno.10443
|View full text |Cite
|
Sign up to set email alerts
|

Spatial food‐web structure in the eastern tropical Pacific Ocean based on compound‐specific nitrogen isotope analysis of amino acids

Abstract: The effective evaluation of trophic interactions in pelagic food webs is essential for understanding food web ecology, conservation biology, and management. We tested the applicability of compound‐specific isotope analysis of amino acids (CSIA‐AA) for (1) characterizing trophic positions (TPs) of nine species from four trophic groups (tunas, squids, myctophids, and euphausiids) within a pelagic food web in the eastern tropical Pacific (ETP) Ocean, (2) evaluating trophic discrimination factors (TDFs) of each tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 69 publications
(186 reference statements)
3
36
0
Order By: Relevance
“…Similar to other organisms in the eastern Pacific (e.g., copepods, laternfishes and tuna; Popp et al, 2007;Olson et al, 2010;Hetherington et al, 2017), olive ridley bulk skin δ 15 N values showed a tendency to be more 15 N-enriched in higher latitudes. Often, differences in δ 15 N values of consumers may be driven by trophic differences among spatially discrete foraging populations (Vander Zanden and Rasmussen, 2001).…”
Section: Trophic Positionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar to other organisms in the eastern Pacific (e.g., copepods, laternfishes and tuna; Popp et al, 2007;Olson et al, 2010;Hetherington et al, 2017), olive ridley bulk skin δ 15 N values showed a tendency to be more 15 N-enriched in higher latitudes. Often, differences in δ 15 N values of consumers may be driven by trophic differences among spatially discrete foraging populations (Vander Zanden and Rasmussen, 2001).…”
Section: Trophic Positionsupporting
confidence: 53%
“…For example, TPs of tuna, adult leatherbacks, lanternfishes, dragonfishes, and zooplankton do not change across ocean basins Olson et al, 2010;Choy et al, 2012;Hetherington et al, 2017). This underscores the uniqueness of detecting a potential trophic shift on the Costa Rica Dome.…”
Section: Costa Rica Dome-a Unique Food Web?mentioning
confidence: 93%
“…Corrected regression lines with a common slope of 1.51 based on the ANCOVA for each group are shown with those in previous studies for other epipelagic ecosystems in the Pacific Ocean (Aita et al, 2011). Mean stable isotopic signatures in muscle tissues of yellowfin tuna as an apex predator in the subtropical waters in previous studies (Graham, 2007;Olson et al, 2010;Revill, Young, & Lansdell, M., 2009) believed to reflect the variable stable isotopic signatures in primary producers where the tuna have foraged (Hetherington et al, 2017;Lorrain et al, 2015;Olson et al, 2010). Although shift and homogenization of isotopic signatures occur by migration between regions in which isotopic signatures of primary producers are different, the isotopic signature of yellowfin tuna collected in Hawaii is clearly lower than those caught in other areas of the Pacific (Figure 7), suggesting that the diazotroph-dominant community within the subtropical region contributes substantially to the apex predators.…”
Section: Geographical Pattern Of the Diazotrophic Contribution Of Nmentioning
confidence: 88%
“…Although yellowfin tuna is categorized as a highly migratory species, it tends to remain in a confined region when it encounters a preferable feeding site (Schaefer, Fuller, & Block, ). This explains the regional difference of the nitrogen stable isotope signatures in yellowfin tuna in the Pacific, which is believed to reflect the variable stable isotopic signatures in primary producers where the tuna have foraged (Hetherington et al, ; Lorrain et al, ; Olson et al, ). Although shift and homogenization of isotopic signatures occur by migration between regions in which isotopic signatures of primary producers are different, the isotopic signature of yellowfin tuna collected in Hawaii is clearly lower than those caught in other areas of the Pacific (Figure ), suggesting that the diazotroph‐dominant community within the subtropical region contributes substantially to the apex predators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation